2016
DOI: 10.1039/c5nr07842c
|View full text |Cite
|
Sign up to set email alerts
|

Visible light response, electrical transport, and amorphization in compressed organolead iodine perovskites

Abstract: Recent scientific advances on organic-inorganic hybrid perovskites are mainly focused on the improvement of power conversion efficiency. So far, how compression tunes their electronic and structural properties remains less understood. By combining in situ photocurrent, impedance spectroscopy, and X-ray diffraction (XRD) measurements, we have studied the electrical transport and structural properties of compressed CH3NH3PbI3 (MAPbI3) nanorods. The visible light response of MAPbI3 remains robust below 3 GPa whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
105
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(112 citation statements)
references
References 42 publications
6
105
0
1
Order By: Relevance
“…10). 9,10 It is interesting to observe that, while this lowpressure phase transition occurs at the same pressure for all the experiment carried out so far on the MAPbI3, i.e. refs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…10). 9,10 It is interesting to observe that, while this lowpressure phase transition occurs at the same pressure for all the experiment carried out so far on the MAPbI3, i.e. refs.…”
Section: Resultsmentioning
confidence: 99%
“…Also in this work, the authors did not used any P-transmitting medium, thus suggesting, as in the case of ref. 9, that these structural data may be strongly dependent upon the absence of hydrostaticity in their measurements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24] The pressure response of the optical and electronic properties of MAPbI 3 has also been investigated to delve into the structure-property relationship of perovskites. [24][25][26][27] Formamidinium lead bromide (NH 2 CH=NH 2 PbBr 3 , FAPbBr 3 ) possesses a bandgap of 2.23 eV under ambient conditions, which makes it more suitable for tandem application than MAPbBr 3 . 28 Hanusch et al reported a striking advantage of the FAPbBr 3 perovskites, that is, the material could be processed in a planar heterojunction configuration without a mesoporous scaffold for charge extraction.…”
mentioning
confidence: 99%
“…221), in which all the BX 6 octahedra show B-X-B angles of 908 8.T his arrangement of untilted octahedra can be described in Glazer notation [14,15] as a 0 a 0 a 0 .Among the Pb-based methylammonium (MA) halide perovskites (ionic A = CH 3 NH 3 + or MA;X= Cl À ,B r À ,I À ;B= Pb 2+ ), the band gaps of MAPbCl 3 ,M APbBr 3 ,a nd MAPbI 3 are reported as around 3.1, 2.3, and 1.5 eV,r espectively. Although pressureinduced synchrotron powder X-ray diffraction (XRD) of MAPbI 3 was reported recently, [18] extraction of high-pressure lattice parameters,t he unambiguous determination of crystal symmetry and the refinement of atomic fractional coordinate are challenging. [17] Therefore,M APbI 3 is the preferred material.…”
mentioning
confidence: 99%